Determination of Dolus and Tempus Delicti on the Crime of Hate Speech Conducted from Outside the State of Indonesia by Using Social Media Facilities - I Wayan Budha Yasa (Media Komunikasi FPIPS, 2021)
The development of information technology, media and communication at this time has changed the behavior of society and human civilization globally. In this regard, in addition to the positive benefits arising from the development of information technology and so on, such as the emergence of facilities or media that can make it easier for humans to work, there are also negative impacts, such as crimes in cyberspace. One of the crimes in cyberspace in question is hate speech. These actions can be classified into criminal acts, because these actions will have an impact on society in general. Moreover, this action was carried out from outside the State of Indonesia using social media facilities, of course it would be very difficult to determine the place (locus delicti) and time (tempus delicti) to try the perpetrators of the hate speech crime. For this reason, it is necessary to know how to determine the locus and tempus delicti of the crime or crime in question.